Preliminary studies and characterization of oil palm frond leaves silica-based bonded lipase / Adikwu Gowon Jacob and Roswanira Abdul Wahab - Jacob, Adikwu Gowon; Abdul Wahab, Roswanira (UiTM Press, 2022)
Despite the benefits of bio-based enzyme biocatalysts, high production-and separation from reaction mixture costs hinders their industrial applications. Whereas enzymes are usually immobilized on solid supports for improving stability, recovery and activity, there are concerns that the synthetic and non-biodegradable nature of the support materials could negatively impact the environment. Thus, there is a need for new enzyme supports to be prepared from sustainable and readily available biodegradable resources. This present study proposed the fabrication of low-cost support comprising co-precipitated magnetic nanoparticles, graphene oxide, and silica extracted from oil palm frond leaves (OPFL) for immobilization of Candida rugosa lipase (CRL). The support and immobilized lipase were characterized by Raman spectroscopy, atomic force microscopy, FESEM, and FTIR methods. Raman spectral data revealed that the GO was successfully synthesized from graphite. Atomic power and field-emission scanning micrographs confirmed the presence of CRL on the support's surface. The FTIR results showed amide bonds at 1390, 1500, and 1650 cm‒1, which corroborated the covalent bonded CRL on the support. The optimum condition to immobilize CRL onto the support was a 16 h immobilization time with pentanoic acid to ethanol molar ratio of 1:1. These conditions favored the highest protein loading of 15.17 ± 0.06 mg/g, and a good immobilization efficiency of 72.34 ± 0.64 %, which gave the highest ethyl pentanoate (EP) conversion of 74.46 ± 0.74 % (specific activity = 56.77 ± 1.42 μmol/min/g) than 48.75 ± 0.70 % for the free CRL. The findings conveyed that the developed support had adequately activated and stabilized the CRL for substantial production of EP and permitted the recovery of the immobilized lipase by induced magnetism.